Die ontstaan van belydenisskrifte gedurende die sestiende en sewentiende eeu - Dreyer, Wim (Hervormde teologiese studies, 1997)
The origin of Reformed confessions during the sixteenth and seventeenth centuries. This article examins the background, history and development of Reformed confessions in the sixteenth and seventeenth centuries, but especially the Swiss and French confessions which influenced the Belgic Confession of Faith, the Heidelberg Catechism and the Articles of Dordt. The premise is that if we really want to understand and interpret confessions, they must be read against their historical, theological and political background. At the same time confessions cannot be properly understood in isolation from their present context, that is, being confessions of the church. Confessions are not only historical documents, but of immense importance to the church which must confess its faith in the present.